The etiological, demographic, and seasonal characteristics of patients with dizziness and vertigo - Atalay, Fatma; Kars, Ayhan; Topal, Kubra; Anbar, Sezai Sacid; Yavuz, Zeynep (SelSistem, 2023)
Background/Aim: Vestibular disorders are common and can negatively affect quality of life and result in workforce losses; they can also be life-threatening diseases. As a result, studies of their etiology and treatment approaches are of particular importance. The aim of this study was to analyze the etiological, demographic, and seasonal characteristics of patients presenting to the Kastamonu Training and Research Hospital Ear, Nose, and Throat (ENT) clinic in Kastamonu, Turkey complaining of vertigo/dizziness. Methods: In this retrospective cohort study, the files of 1033 patients who presented at the clinic with a report of vertigo/dizziness between September 2020 and September 2021 were examined. The patients’ demographic characteristics, presentation dates, and diagnoses were recorded. Results: Six hundred and fifty-one patients (63%) were female, and the mean age of the patient cohort was 50.3 years (standard deviation: 16.0 years). Six hundred and twenty-seven patients (60.7%) were identified with chronic subjective dizziness, 302 (29.2%) were identified with benign paroxysmal positional vertigo, 18 (1.7%) were identified with vestibular migraine, 7 (0.7%) were identified with bilateral vestibulopathy, 41 (4.0%) were identified with unilateral vestibulopathy, 16 (1.5%) were identified with vestibular neuritis, 6 (0.6%) were identified with Meniere’s disease, 10 (1.0%) were identified with central vertigo/dizziness, 3 (0.3%) were identified with labyrinthitis and 3 (0.3%) were identified with another form of vertigo/dizziness. An increase in the number of cases was observed in the spring, and the number of patients presenting with vertigo/dizziness decreased thereafter and reached a minimum in the fall (P<0.001). Conclusion: The most common vestibular disorder was chronic subjective dizziness. Vestibular disorders are more common in women and in the spring season. Although ENT specialists generally focus on pathologies of the ear, vertigo/dizziness are symptoms that may involve several etiologies. Meticulous clinical examinations should be performed; the etiological cause and clinical diagnosis in these cases will dictate additional tests to be requested and therapeutic strategies. Due to the broad diagnostic spectrum of these cases, a multidisciplinary approach is also critical.
Keywords: 3. Good health